PENGARUH PEMBELAJARAN BERDIFERENSIASI PADA HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Siska Ulandari, Amanda; Idris, Muhamad; Budi Irawan, David (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of differentiated learning on the learning outcomes of fourth-grade elementary school students in science. The research was motivated by low student engagement in learning, difficulty understanding the material, and the use of conventional learning models. This study used a quantitative method with a quasi-experimental type and a Non-Equivalent Control Group Design. The research sample consisted of 55 fourth-grade students of SD Negeri 17 Palembang consisting of an experimental class and a control class. Data collection techniques used tests and documentation, while data analysis was carried out through hypothesis testing using an independent sample t-test. The results showed that the average posttest score of the experimental class was 80.65, higher than the control class at 71.56. The results of the hypothesis test obtained a Sig. (2-tailed) value = 0.029 <0.05, so it can be concluded that there is a significant influence of differentiated learning on the learning outcomes of fourth-grade students in SD Negeri 17 Palembang